CHALLENGES AFFECTING TEACHERS’ COMPETENCY IN IMPLEMENTING THE 21ST-CENTURY CURRICULUM IN SECONDARY SCHOOLS IN SOUTH-WEST NIGERIA - Aina, Gbenga (Mutiara Intelektual Indonesia Press, 2025)
This study aimed to explore the challenges impacting teachers' competency in implementing the 21st-century curriculum in secondary schools across South-West Nigeria. A descriptive cross-sectional survey design was utilized, with the target population consisting of secondary school teachers from the six South-West states: Ondo, Oyo, Osun, Ekiti, Lagos, and Ogun. A total of 860 teachers were selected using a multistage sampling technique to ensure representation. Data were collected through a 15-item questionnaire developed by the researcher, titled